Cross-species transmission, evolution and zoonotic potential of coronaviruses - Li, Qian; Shah, Taif; Wang, Binghui; Qu, Linyu; Wang, Rui; Hou, Yutong; Baloch, Zulqarnain; Xia, Xueshan (Frontiers in Cellular and Infection Microbiology, 2023)
Coronaviruses (CoVs) continuously evolve, crossing species barriers and spreading across host ranges. Over the last two decades, several CoVs (HCoV-229E, HCoV-NL63, HCoV-HKU1, HCoV-OC43, SARS-CoV, MERS-CoV, and SARS-CoV-2) have emerged in animals and mammals, causing significant economic and human life losses. Due to CoV cross-species transmission and the evolution of novel viruses, it is critical to identify their natural reservoiurs and the circumstances under which their transmission occurs. In this review, we use genetic and ecological data to disentangle the evolution of various CoVs in wildlife, humans, and domestic mammals. We thoroughly investigate several host species and outline the epidemiology of CoVs toward specific hosts. We also discuss the cross-species transmission of CoVs at the interface of wildlife, animals, and humans. Clarifying the epidemiology and diversity of species reservoirs will significantly impact our ability to respond to the future emergence of CoVs in humans and domestic animals.